Altered Tumor-Cell Glycosylation Promotes Metastasis - Häuselmann, Irina; Borsig, Lubor (Frontiers in Oncology, 2014)
Malignant transformation of cells is associated with aberrant glycosylation presented on the cell-surface. Commonly observed changes in glycan structures during malignancy encompasses aberrant expression and glycosylation of mucins; abnormal branching of N-glycans; and increased presence of sialic acid on proteins and glycolipids. Accumulating evidence supports the notion that the presence of certain glycan structures correlates with cancer progression by affecting tumor cell invasiveness, ability to disseminate through the blood circulation and to metastasize in distant organs. During metastasis tumor cell-derived glycans enable binding to cells in their microenvironment including endothelium and blood constituents through glycan-binding receptors - lectins. In this review we will discuss current concepts how tumor cell-derived glycans contribute to metastasis with the focus on three types of lectins: siglecs, galectins and selectins. Siglecs are present on virtually all hematopoetic cells and usually negatively regulate immune responses. Galectins are mostly expressed by tumor cells and support tumor cell survival. Selectins are vascular adhesion receptors that promote tumor cell dissemination. All lectins facilitate interactions within the tumor microenvironment and thereby promote cancer progression. The identification of mechanisms how tumor glycans contribute to metastasis may help to improve diagnosis, prognosis and aid to develop clinical strategies to prevent metastasis.